Systemic lupus erythematosus: updated insights on the pathogenesis, diagnosis, prevention and therapeutics - Xiaofeng Dai; Yuting Fan; Xing Zhao (Signal Transduction and Targeted Therapy)
Abstract Systemic lupus erythematosus (SLE) is a chronic inflammatory illness with heterogeneous clinical manifestations covering multiple organs. Diversified types of medications have been shown effective for alleviating SLE syndromes, ranging from cytokines, antibodies, hormones, molecular inhibitors or antagonists, to cell transfusion. Drugs developed for treating other diseases may benefit SLE patients, and agents established as SLE therapeutics may be SLE-inductive. Complexities regarding SLE therapeutics render it essential and urgent to identify the mechanisms-of-action and pivotal signaling axis driving SLE pathogenesis, and to establish innovative SLE-targeting approaches with desirable therapeutic outcome and safety. After introducing the research history of SLE and its epidemiology, we categorized primary determinants driving SLE pathogenesis by their mechanisms; combed through current knowledge on SLE diagnosis and grouped them by disease onset, activity and comorbidity; introduced the genetic, epigenetic, hormonal and environmental factors predisposing SLE; and comprehensively categorized preventive strategies and available SLE therapeutics according to their functioning mechanisms. In summary, we proposed three mechanisms with determinant roles on SLE initiation and progression, i.e., attenuating the immune system, restoring the cytokine microenvironment homeostasis, and rescuing the impaired debris clearance machinery; and provided updated insights on current understandings of SLE regarding its pathogenesis, diagnosis, prevention and therapeutics, which may open an innovative avenue in the fields of SLE management.